2015
DOI: 10.1016/j.jpainsymman.2014.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Symptom Expression in the Last Seven Days of Life Among Cancer Patients Admitted to Acute Palliative Care Units

Abstract: Context The symptom burden in the last week of life of patients with advanced cancer has not been well characterized. Objectives To examine the frequency, intensity, and predictors for symptoms in the last seven days of life among patients who were able to communicate and died in an acute palliative care unit (APCU). Methods We systematically documented the Edmonton Symptom Assessment System (ESAS) daily and 15 symptoms twice daily on consecutive advanced cancer patients admitted to APCUs at M.D. Anderson … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
90
0
6

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(102 citation statements)
references
References 32 publications
5
90
0
6
Order By: Relevance
“…Cancer patients near end of life report more severe symptoms than other cancer patients 4 . Hui et al found that patients in the last week of life still suffer from high symptom burden mainly dyspnea, fatigue and drowsiness; and according to them, these symptoms may be unavoidable in this group of patients in spite of high quality supportive care 5 . The prevalence of pain in cancer patients varies significantly between studies.…”
Section: The World Health Organization Defines Palliative Care As "Anmentioning
confidence: 99%
“…Cancer patients near end of life report more severe symptoms than other cancer patients 4 . Hui et al found that patients in the last week of life still suffer from high symptom burden mainly dyspnea, fatigue and drowsiness; and according to them, these symptoms may be unavoidable in this group of patients in spite of high quality supportive care 5 . The prevalence of pain in cancer patients varies significantly between studies.…”
Section: The World Health Organization Defines Palliative Care As "Anmentioning
confidence: 99%
“…Patients with cancer diagnoses were the next studied population of focus (n=13), [38][39][40][41][42][43][44][45][46][47][48][49][50] followed by patients with interstitial lung disease (n=8), [51][52][53][54][55][56][57][58] and lastly one study focussed on patients with Huntington's disease (Table 1) Page S35…”
Section: Resultsmentioning
confidence: 99%
“…22 In another study done by Hui et al, 74-83% of patients in palliative care units had anorexia. 30 Anorexia may be because of the direct effect on oral intake due to dysphagia, early satiety, xerostomia, nausea/ vomiting, taste disturbance, mucositis, constipation, bowel obstruction, dental issue, etc., or, because of indirect effect on oral intake due to delirium, drowsiness, dyspnea, depression, etc. Inflammatory response and neurohormonal changes may also cause loss of appetite.…”
Section: Discussionmentioning
confidence: 99%
“…31 Refractory cachexia is seen in the last days of life due to inflammatory response, hyper metabolism and overall catabolic state with muscle loss. 30 Cancer related cachexia is seen in 50-80% of cancer patients with advanced and metastatic disease. 32 Cachexia weakens the body and promotes further spread of cancer.…”
Section: Discussionmentioning
confidence: 99%